2013
DOI: 10.1002/jbmr.2070
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Establishment of Allelic Gαs Silencing as a Plausible Explanation for Delayed Onset of Parathyroid Hormone Resistance Owing to Heterozygous Gαs Disruption

Abstract: Pseudohypoparathyroidism type-Ia (PHP-Ia), characterized by renal proximal tubular resistance to parathyroid hormone (PTH), results from maternal mutations of GNAS that lead to loss of Gαs activity. Gαs expression is paternally silenced in the renal proximal tubule, and this genomic event is critical for the development of PTH-resistance, as patients display impaired hormone action only if the mutation is inherited maternally. The primary clinical finding of PHP-Ia is hypocalcemia, which can lead to various ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 74 publications
(199 reference statements)
2
74
0
5
Order By: Relevance
“…Resistance to TSH is a common finding in PHP1A patients, and hypothyroidism is one of the main symptoms of the multihormonal resistance in PHP, affecting more than 90% of PHP1A patients [1,3,17,21,22]. In 1982, Mallet et al [23] showed that there was no increase in intracellular cAMP in response to TSH in membrane thyroid from patients with PHP.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to TSH is a common finding in PHP1A patients, and hypothyroidism is one of the main symptoms of the multihormonal resistance in PHP, affecting more than 90% of PHP1A patients [1,3,17,21,22]. In 1982, Mallet et al [23] showed that there was no increase in intracellular cAMP in response to TSH in membrane thyroid from patients with PHP.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of TSH resistance is often present at birth and can lead to the misdiagnosis of congenital hypothyroidism 24,30 , whereas PTH resistance develops during childhood [31][32][33][34] . Similarly, brachydactyly develops progressively and usually becomes obvious before puberty 34,35 .…”
Section: Methodsmentioning
confidence: 99%
“…In patients with PHP1A, resistance to PTH is usually absent at birth and evolves over life (from 0.2 years to 22 years) 18,31,34 , while the clinical manifestations typically occur later. These data suggest that PTH resistance begins in early childhood, and the resultant changes in serum levels of calcium and phosphorus develop gradually, at some point during adulthood 31,32,[66][67][68] . The first biochemical abnormalities to become apparent are elevated serum levels of PTH and elevated serum levels of phosphorus, followed by hypocalcaemia.…”
Section: Main Clinical Componentsmentioning
confidence: 99%
“…Age of onset of the hormone resistance is quite variable among mutation‐positive individuals and can be delayed for several years. This latency of PTH resistance in patients with PHP1a has been attributed to a gradual development of paternal Gs‐alpha silencing in target tissues 4. Therefore, genetic screening of family members can be useful for presymptomatic diagnosis.…”
Section: Figurementioning
confidence: 99%